Leadership and Nigeria's Regional Hegemonic Quest in Africa: A Critical Discus - GAMBO Nanven Audu; PULDU Samdi Gloria; KUMS Simon Nankap (International Studies Journal)
The aftermath of the Cold War and the fall of the Berlin wall re-mirrored and reconfigured the nature and patterns of game and/or relations in the international ambiance. The international political system experienced an unprecedented and remarkable shift from a United States (US) led unipolar global order to a fresh wave or emergence of multiple competitors. This changed global context has led to continuing interest in (and increasing research focus on) regions, regional order and regional powers in terms of their roles (with other regional/state actors) in the international system. However,Nigeria with its endowed numerous natural and human resources which she utilized for the betterment of Africa; prompted her to assume the leadership role which she did by leading other African countries in the decolonization struggles and the fight against apartheid regime in South Africa. Thus, Nigeria's leadership role towards achieving stability and development in Africa cannot be overemphasized. These prominent role and contribution of Nigeria to Africa qualifies it more to be a regional hegemon among other contenders in the continent; but challenges such as poor leadership, unending terrorism, human rights abuses, widespread corruption, poverty, faulty democratic/electoral processes, non-strategic foreign policy among others continue to mar and/or diminish her chances to attain the status of a regional hegemon. The study makes use of hegemonic stability theory to appraise Nigeria's role and contribution in Africa as an essential tool for the country to assume regional hegemon in the continent. This study employs a qualitative method of analysis; as secondary sources of data were used in collecting data. The paper aims at examining the strategic nature of Nigeria's foreign policy and its leadership quality in booking a place for her in her quest to become a continental hegemon. The study concludes and recommends that until Nigeria looks inward by addressing its internal dynamics and/or challenges (unending terrorism, widespread corruption, poor leadership, faulty electoral processes, acute human rights abuses, etc), its quest to become a regional hegemon remains an illusion.